2011
DOI: 10.1007/s00270-011-0188-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Two Different n-Butyl-2-Cyanoacrylates for the Embolization of Varicoceles: A Prospective, Randomized, Blinded Study

Abstract: NBCA and NBCA-MS are equally efficient and safe glues for embolization of varicoceles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Indeed, percutaneous embolization has the advantage of being an outpatient procedure with a faster return to normal activities, a considerably lower cost and a lower recurrence rate than is the case for surgery (6). The use of many different embolic agents, such as gelatin sponge, stainless steel coils, Amplatzer vascular plugs, detachable balloons, cyanoacrylate glues or sclerosing agents has been reported (7)(8)(9)(10)(11)(12)(13)(14)(15). However, to our knowledge, there are no data in the literature regarding the comparison of the different embolic materials currently available on the market for the treatment of varicocele in terms of efficacy, tolerance, radiation and recurrence rates.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Indeed, percutaneous embolization has the advantage of being an outpatient procedure with a faster return to normal activities, a considerably lower cost and a lower recurrence rate than is the case for surgery (6). The use of many different embolic agents, such as gelatin sponge, stainless steel coils, Amplatzer vascular plugs, detachable balloons, cyanoacrylate glues or sclerosing agents has been reported (7)(8)(9)(10)(11)(12)(13)(14)(15). However, to our knowledge, there are no data in the literature regarding the comparison of the different embolic materials currently available on the market for the treatment of varicocele in terms of efficacy, tolerance, radiation and recurrence rates.…”
Section: Introductionmentioning
confidence: 65%
“…Additional coils are then placed in the upper part of the spermatic vein, as we usually did in our study. In Europe, the main cyanoacrylate glues used for medical purposes today are NBCA (Histoacryl ® ) and NBCA-MS (Glubran ® 2), a copolymer of NBCA with a lower temperature of polymerization (10,22). The endothelium of the vessel is damaged as a result of the heat generated by the polymerization reaction of the glue.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies based on venography and with large number of patients report a bilateral varicocele in 25% [8][9][10]. In studies using different diagnostic tools, bilateral varicocele was reported in a range between 40% and 60% [11][12].…”
Section: Presentation Incidence and Epidemiology Of Varicocelesmentioning
confidence: 99%
“…Only embolization with high viscosity liquids (glue) has a reported low technical failure rate (<1%) and lower recurrence rates (< 2%) [10,23,36,37]. The low technical failure rate is probably related to the use of a coaxial catheter system.…”
Section: Non-liquid Embolicsmentioning
confidence: 99%
See 1 more Smart Citation